Fusarium proliferatum strains change fumonisin biosynthesis and accumulation when exposed to host plant extracts. Issue 6 (June 2016) - Górna, Karolina; Pawłowicz, Izabela; Waśkiewicz, Agnieszka; Stępień, Łukasz
Abstract: Fumonisin concentrations in mycelia and media were studied in liquid Fusarium proliferatum cultures supplemented with host plant extracts. Furthermore, the kinetics of fumonisin accumulation in media and mycelia collected before and after extract addition was analysed as well as the changes in the expression of the FUM1 gene. Fumonisin content in culture media increased in almost all F. proliferatum strains shortly after plant extracts were added. The asparagus extract induced the highest FB level increase and the garlic extract was the second most effective inducer. Fumonisin level decreased constantly until 14th day of culturing, though for some strains also at day 8th an elevated FB level was observed. Pineapple extract induced the highest increase of fum1 transcript levels as well as fumonisin synthesis in many strains, and the peas extract inhibited fungal growth and fumonisin biosynthesis. Moreover, fumonisins were accumulated in mycelia of studied strains and in the respective media. Highlights: Fumonisin accumulation by Fusarium proliferatum is influenced by host plant extracts. No host-specific reaction of individual strains was observed. FUM1 gene expression was induced particularly by pineapple and maize extracts. Fumonisins were accumulated both in mycelia and respective culture media.